The Stones of Athens - Wycherley, R. E. (Richard Ernest) (Book collections on Project MUSE., 1978)
Interpreting the monuments of Athens in light of literature, R. E. Wycherley brings before us the city the ancients knew. Philosophers, statesmen, travelers, dramatists, poets, private citizens-the words of all these suggest how the city looked at various periods, how its monuments came to be built, and how they served the people in daily life. Professor Wycherley concentrates on the classical period, illustrating his work with plans, reconstructions, and photographs.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.